2016
DOI: 10.1039/c6nr06837e
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O/g-C3N4nanocomposites: an insight into the band structure tuning and catalytic efficiencies

Abstract: We demonstrate an easy and scalable room-temperature synthesis of CuO nanoparticle incorporated graphitic carbon nitride composites without the aid of any inert atmosphere. First principles calculations based upon density functional theory, in addition to the experimental validations, have been employed to investigate the electronic and optical properties of the nanocomposites. An insight into the band structure tunability, phase stabilisation and the dependancy of the catalytic properties of the nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 68 publications
0
37
0
Order By: Relevance
“…Figure b shows the high‐resolution XPS spectrum of C 1 s, in which there are peaks at 284.7 and 288.2 eV according to the peak fitting result. The peak at 288.2 eV corresponds to C −N=C in the heterocycle rings, and the peak at 284.7 eV is ascribed to C=C in adventitious carbon . The corresponding binding energies of N 1 s spectra are determined to be 398.8 eV, 400.0 eV, and 401.3 eV (Figure c), corresponding to the structure of g‐C 3 N 4 , further indicating the presence of g‐C 3 N 4.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Figure b shows the high‐resolution XPS spectrum of C 1 s, in which there are peaks at 284.7 and 288.2 eV according to the peak fitting result. The peak at 288.2 eV corresponds to C −N=C in the heterocycle rings, and the peak at 284.7 eV is ascribed to C=C in adventitious carbon . The corresponding binding energies of N 1 s spectra are determined to be 398.8 eV, 400.0 eV, and 401.3 eV (Figure c), corresponding to the structure of g‐C 3 N 4 , further indicating the presence of g‐C 3 N 4.…”
Section: Resultsmentioning
confidence: 88%
“…Constructing a heterojunction is an effective strategy to enhance carrier transfer between semiconductors . The g‐C 3 N 4 ‐Cu 2 O heterojunction is a prospective material for the degradation of organic pollutants because of its high oxidation capacity, low toxicity, and chemical stability . However, the photocatalytic efficiency needs to be further improved due to g‐C 3 N 4 block agglomeration, poor dispersion, and rapid recombination of the light‐generated electron–hole pair.…”
Section: Introductionmentioning
confidence: 99%
“…The V FB is approximately equal to the conduction band edge potential (V CB ) or the valence band edge potential (V VB ) in the case of an n-type or a p-type semiconductor, respectively [37]. As shown in Fig.…”
Section: Photoelectrochemical Propertymentioning
confidence: 99%
“…It is reported that there is almost no H 2 was produced on bare g‐C 3 N 4 . The hydrogen production rate of g‐C 3 N 4 was improved by preparing g‐C 3 N 4 with various structures and morphologies, doping metal and nonmetallic atoms, loading cocatalysts, etc. The supported cocatalyst can effectively reduce the recombination of photogenerated carriers and improve the hydrogen production activity of g‐C 3 N 4 due to reduction of Schottky barrier …”
Section: Introductionmentioning
confidence: 99%